327 Effects of Inclusion of Amaferm on Animal Performance, Chewing Activity, and Nutrient Digestibility of Backgrounding Beef Heifers Fed Either a Sorghum Silage- or a Byproducts-based Diet. (8th October 2021) - Podversich, Federico; Tarnonsky, Federico; Bollatti, Juan; da Silva, Gleise Medeiros; Schulmeister, Tessa M; Martinez, Juan Vargas; Heredia, Daniella C; Ipharraguerre, Ignacio R; Dubeux, Jose C B; Ferrareto, Luiz; Gonella-Diaza, Angela Maria M; Chebel, Ricardo; et al.
Abstract: Eighty-four Angus crossbred heifers (13 ± 1 mo, 329.5 ± 61.92 kg of BW) were used in a generalized randomized block design with a 2 × 2 factorial arrangement of treatments. The objective was to evaluate the effect of a feed additive inclusion under two growing diets. Factors included: 1) diet type (whole plant sorghum silage- or byproducts-based diet) and 2) feed additive inclusion [Amaferm (Aspergillus oryzae (extract)] included at 0 or 0.02% of the diet DM. This resulted in four treatments: sorghum-control (SC), sorghum-amaferm (SA), byproducts-control (BC) and byproducts-amaferm (BA). Heifers were housed in 12 pens (108 m 2 /pen; 7 heifers/ pen) equipped with GrowSafe technology, to measure individual dry matter intake (DMI). After a 14-d adaptation, BW was measured every 14 d, during 56 days, and chewing activity was monitored through collar-mounted HR-Tags (SCR Engineers Ltd., Netanya, Israel). Apparent total tract digestibility was measured on 10 heifers per treatment after the 56-d performance period, using indigestible NDF as a marker. Heifers fed the byproducts diet had (P ≤ 0.01) greater DMI as % of BW (2.92 vs. 2.59%) and greater average daily gain (1.16 vs. 0.68 kg/d). Amaferm improved gain-to-feed ratio by 15% in the byproducts diet (P ≤ 0.05) but it had no effect in the sorghum silage diet (P = 0.59). Conversely, Amaferm inclusion increased apparent total tract organic matter digestibility in the sorghum silage diet (SC = 49.8 vs. SA = 55.9%; P ≤ 0.01), whereas reduced it in the byproducts diet (BC = 65.8 vs. BA = 61.7%; P ≤ 0.05). Heifers fed a sorghum silage-based diet had (P ≤ 0.01) 39 and 63% greater chewing in min/d and min/kg of DMI, respectively; however, chewing in min/kg of NDF intake was similar across diets (average 111.3 min/kg of NDF intake).